Kajian Analisis Faktor pada Faktor yang Mempengaruhi Produksi Padi di Nagari Cupak Kabupaten Solok - Rohadatul Aisy; Devni Prima Sari (Journal of Mathematics UNP, 2023)
Solok district is the largest rice producing center in West Sumatra, known as "Bareh Solok", with most of the population working as farmers. Increased production is influenced by factors such as land area, labor, seeds, fertilizers, capital, pesticides, and irrigation. These seven factors are interconnected and related to each other, so the purpose of this study was to determine the factors that influence rice production in Nagari Cupak, Gunung Talang District, Solok Regency. The type of research used is applied research. This study has a sample of 89 respondents. Furthermore, in the analysis using factor analysis method. The results of this study indicate that the first factor consists of land area, labor, seeds and pesticides. The second factor consists of fertilizer, capital and pesticide variables